Antidepressants - Preclinical, Clinical and Translational Aspects 2019
DOI: 10.5772/intechopen.83743
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Use of Antidepressants to Treat Alcohol Use Disorders and Depression Comorbidity: The Role of Neurogenesis

Abstract: Patients with alcohol use disorders (AUDs) are frequently treated with antidepressant drugs (ADs), but clinical evidence of their efficacy is contradictory. Considering that ADs are thought to produce their therapeutic effects partially by increasing hippocampal plasticity and neurogenesis (HN), and that both AUDs and depression share a potential for the disruption of these neuroplastic processes, one could reasonably wonder whether the poor efficacy of AD treatment could be explained by the inability of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 115 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Thereby, the identified dual pathway framework may echo the inconsistent findings in previous research. For instance, some studies have reported that antidepressants may improve AUD treatment outcomes (Chan et al, 2015;Li et al, 2020;McHugh & Weiss, 2019;Ostacher, 2007;Pettinati, 2004), while others have found little or no benefit (Iovieno et al, 2011;Nunes & Levin, 2004;Torrens et al, 2005), or even a negative effect (Ballesta, Alén, et al, 2019;Brookwell et al, 2014;Dundon et al, 2004;Muhonen et al, 2008;Yoon & Petrakis, 2018;Zhou et al, 2015). Our findings might help to reconcile some of these conflicting results by suggesting that the benefits of antidepressants no effect on alcohol-related outcomes (Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Thereby, the identified dual pathway framework may echo the inconsistent findings in previous research. For instance, some studies have reported that antidepressants may improve AUD treatment outcomes (Chan et al, 2015;Li et al, 2020;McHugh & Weiss, 2019;Ostacher, 2007;Pettinati, 2004), while others have found little or no benefit (Iovieno et al, 2011;Nunes & Levin, 2004;Torrens et al, 2005), or even a negative effect (Ballesta, Alén, et al, 2019;Brookwell et al, 2014;Dundon et al, 2004;Muhonen et al, 2008;Yoon & Petrakis, 2018;Zhou et al, 2015). Our findings might help to reconcile some of these conflicting results by suggesting that the benefits of antidepressants no effect on alcohol-related outcomes (Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…About half of patients with AUD reporting depression symptoms during withdrawal treatment are prescribed antidepressants, even though it is not necessarily indicated, as they may not respond to antidepressants beyond the remission that is achieved with alcohol abstinence (Ballesta, Orio, et al, 2019). In those cases, the prescription of antidepressants is unnecessary, costly and burdensome to those patients (Pary et al, 2017;Pettinati et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations